Characterization of the atmospheric circulation near the Empty Quarter Desert during major weather events - Nelli, Narendra; Francis, Diana; Fonseca, Ricardo; Bosc, Emmanuel; Addad, Yacine; Temimi, Marouane; Abida, Rachid; Weston, Michael; Cherif, Charfeddine (Frontiers in Environmental Science, 2022)
In this study, we characterize the meteorological conditions and planetary boundary layer dynamics in western United Arab Emirates based on 2012–2020 in-situ measurements. This multi-year analysis is then complemented by an intensive field-campaign in winter 2021 from which we address the main patterns of the atmospheric circulation and the boundary layer structure during typical weather events identified in the long-term analysis. We found that, 10-m and 60-m wind speeds are generally below 5 m s−1 and 8 m s−1, respectively, blowing predominantly from a northerly direction. They peak in intensity at around 12–18 Local Time (LT) and 02–09 LT in association with the sea-breeze and the downward mixing of momentum from the nighttime low-level jet, respectively. The wind is stronger in the cold season, varying mostly in response to mid-latitude baroclinic systems, while the proximity of the site to the core of the Arabian Heat Low leads to more quiescent conditions in the summer. Radiation fog is a regular occurrence mostly from December to February owing to the colder nights and weaker wind speeds, with a peak fog occurrence around local sunrise. Sea fog, which develops when the hotter desert air is transported over the cooler Arabian Gulf waters, is advected to the site in the summer. Deep and very deep convective clouds are more common in March-April in association with organized convective systems, with generally reduced cloud cover from May to October. The region of interest exhibits a monthly-mean aerosol optical depth ranging from ∼0.3 in December-January to ∼1.2 in July due to its increased exposure to dust storms in the summer season. Dust activity is also found to peak during winter and spring associated with the intrusion of cold fronts from mid-latitudes.